CD62L test at 2 years of natalizumab predicts progressive multifocal leukoencephalopathy. (6th December 2016) - Pignolet, Béatrice; Schwab, Nicholas; Schneider-Hohendorf, Tilman; Bucciarelli, Florence; Biotti, Damien; Averseng-Peaureaux, Delphine; Outteryck, Olivier; Ongagna, Jean-Claude; de Sèze, Jérôme; Brochet, Bruno; Ouallet, Jean-Christophe; Debouverie, Marc; et al.
Abstract : Flashes of light or phosphenes are the sensation of light without light actually entering the eye. This phenomenon can be evoked by stimulation of the retina or the visual cortex of the brain and can appear unilaterally or bilaterally. From an ophthalmologic perspective, phosphenes can arise from photoreceptor induction by mechanical, 1, 2 inflammatory, 3 or vascular 4 stimuli. Therefore, it is necessary to determine the origin of phosphenes for further management. We encountered a patient who reported having phosphenes while moving his eyes laterally. We performed various ophthalmologic imaging studies to identify the origin of these phosphenes.